ChemInform Abstract: The Mechanism of the Pauson—Khand Reaction: Hypothesis Experimental Facts, and Theoretical Investigations. Issue 17 (4th April 2013) - Cambeiro, Xacobe C.; Pericas, Miquel A.
Abstract Review: 60 refs.